The comparison of different order of concurrent training on plasma myonectin levels, insulin resistance index and anthropometric characteristics of elderly women - AR Kazemi; R Mizani (فصلنامه ابن سینا, 2014)
Background: Concurrent trainings are a form of exercise conducting two kinds of endurance and resistance training together. The aim of this study was to investigate the comparison of different order of concurrent training on plasma Myonectin levels, insulin resistance index (HOMA) and anthropometric characteristics of elderly women. Materials and methods: Forty women with 55-70 year old with no particular illnesses, were divided randomly into four groups: endurance-resistance, (n=9), resistance-endurance (n=10), interval resistance-endurance (n=12) training, and control group (n=9). Height, weight, BMI, WHR and serum levels of myonectin, glucose, and insulin were measured and recorded before and after performing protocol. Experimental groups participated in concurrent training for eight weeks, three sessions every week, 60min in every session. Univariate (covariance) test was used for analyzing of data. Results: There were no significant differences between experimental groups with control group in Myonectin (p=0.534) and insulin (p=0.37). But, there were significant differences in body mass (p=0.02), BMI (p=0.03), fasting glucose (p=0.001) and HOMA (p=0.028). Significant differences were not seen between experimental groups. Conclusion: Older women can take advantage from concurrent training with any orders of them.